Kepemimpinan Pendidikan Islam Perspektif Agama, Humanis, dan Suku - A, Ansori; Fathoni, Wildan; F, Fatmawati; Anwar, Kasful (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Leadership in Islamic education plays a strategic role in building an educational system that emphasizes not only academic achievement but also the development of students’ character, morals, and spirituality. This article discusses the importance of integrating religious, humanistic, and local wisdom values in Islamic educational leadership, as well as the challenges faced in the era of globalization. Using a library research method and qualitative analysis, this article highlights how the principles of justice, wisdom, trustworthiness, and deliberation serve as the main foundation in decision-making and the management of Islamic educational institutions. The findings indicate that Islamic education leaders must be adaptive, innovative, and able to balance the demands of modernity with the preservation of noble Islamic values and local culture. The integration of religious, humanistic, and cultural perspectives is key to creating an inclusive, relevant, and sustainable Islamic education system.